Experimental mechanics and materials : selected, peer reviewed papers of the International Conference on Experimental Mechanics 2010 (ICEM10), 29 November - 1 December 2010, Legend Hotel Kuala Lumpur, Malaysia - Abdul Nassir bin Ibrahim (Applied mechanics and materials ;, 2011)
This work consists of 48 peer-reviewed papers which were selected from those presented at the International Conference on Experimental Mechanics 2010 (ICEM10), held on the 29th November to 1st December 2010, at the Legend Hotel, Kuala Lumpur, Malaysia. The papers cover the latest research results on experimental mechanics, and offer a timely overview of the subject. Review from Book News Inc.: The 47 selected papers in this collection originally were presented during the International Conference on Experimental Mechanics 2010 held in Kuala Lumpur, Malaysia on November 29-December 1, 2010. Topi.